Warnings : finding Cassandras to stop catastrophes - Clarke, Richard A. (Richard Alan), 1951-; Eddy, R. P. (New York : Ecco, an imprint of HarperCollins Publishers, 2017)
In Greek mythology, Cassandra foresaw calamities, but was cursed by the gods to be ignored. Modern-day Cassandras clearly predicted the disasters of Katrina, Fukushima, the Great Recession, the rise of ISIS, and many others. Like her, they were ignored. There are others right now warning of impending disasters, but how do we know which warnings are likely to be right? Through explorations in a variety of fields, the authors uncover a method to separate the accurate Cassandras from the crazy doomsayers.
Cassandra: From myth to reality -- The spook: Invasion of Kuwait -- The rebuilder: Hurricane Katrina -- The Arabist: The rise of ISIS -- The seismologist: Fukushima Nuclear Disaster -- The accountant: Madoff's Ponzi Scheme -- The inspector: Mine disaster -- The market analyst: The 2008 recession -- The Cassandra coefficient -- The computer scientist: Artificial intelligence -- The journalist: Pandemic disease -- The climate scientist: Sea-level rise -- The weatherman: Nuclear ice age -- The engineer: The internet of everything -- The planetary defender: Meteor strike -- The biologist: Gene editing -- Can you hear her now?
Includes bibliographical references (pages 371-389) and index.
Keywords: Risk communication; Disasters -- Forecasting; Warnings; Emergency management; Emergency management; Disasters -- Forecasting; SOCIAL SCIENCE / Disasters & Disaster Relief; SOCIAL SCIENCE / Future Studies; Disasters -- Forecasting; Emergency management; Risk communication; Warnings